2014
DOI: 10.2217/pgs.13.241
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Landscape of Clopidogrel in North Indians Suggest Distinct Interpopulation Differences in Allele Frequencies

Abstract: This is the largest population-scale genetic epidemiology study that provides a high-resolution map of variants associated with clopidogrel response that could be potentially valuable to clinicians to rationally plan appropriate dosage for therapy in resource poor conditions based on population level allele frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge creation of such a genotype frequency map at the population scale level to guide initial warfarin dosing in clinical practice has not been used before, hence, the value of this approach in improving the outcomes cannot been established at present. Nonetheless, a recent study used a similar approach to create a pharmacogenetic landscape to guide appropriate dosage for the antiplatelet drug clopidogrel among north Indians [40]. This kind of genetic epidemiological analysis provides a platform to predict the drug response and helps in minimizing the associated risk.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge creation of such a genotype frequency map at the population scale level to guide initial warfarin dosing in clinical practice has not been used before, hence, the value of this approach in improving the outcomes cannot been established at present. Nonetheless, a recent study used a similar approach to create a pharmacogenetic landscape to guide appropriate dosage for the antiplatelet drug clopidogrel among north Indians [40]. This kind of genetic epidemiological analysis provides a platform to predict the drug response and helps in minimizing the associated risk.…”
Section: Discussionmentioning
confidence: 99%
“…One study identified lower frequency of the CYP2C19*2 variant in North Indians of Asian descent compared with the global population [ 136 ], while another study suggested comparable frequencies (40–47%) in Asian Indian patients with ischemic heart disease [ 137 ]. A meta-analysis showed that carrier status for LOF genetic variants in CYP2C19 associated with increased risk of adverse clinical events [ 138 ].…”
Section: Regulators Of Responsementioning
confidence: 99%
“…Prevalence of PGx variations have been demonstrated to vary substantially between populations. [65] Depending on the testing platform used, rare variants may be missed [66], including those present in less studied populations, thereby limiting benefit of testing to some population groups due to the prevalence disparities between groups. [67] For minority patients, use of PGx gene panels may return more uncertain findings [68] and providers should disclose this to patients and be prepared for this possibility when discussing test results.…”
Section: Barriers To Test Utilizationmentioning
confidence: 99%